Analisis Peranan Jaringan Sosial pada Pembentukan dan Pemeliharaan Pengelolaan BUMDes yang Demokratis (Studi Kasus: BUMDes Tunas Mandiri, Desa Nglanggeran, Kecamatan Patuk, Kabupaten Gunung Kidul) - L Bambang Harnoto; Prismanto Atmaji; Yuliana Rini Hardanti; Maria Theresia Ernawati (EXERO : Journal of Research in Business and Economics, 2021)
Social networks as the essence of social capital theory have a significant, strategic, and central role in the formation and maintenance of democratic BUMDes governance. This study aims to describe the role of social networks in the formation and maintenance of democratic BUMDes management. This type of research is a case study using descriptive analysis through tables and graphs. The population of this research is all members of BUMDes Tunas Mandiri. The number of samples in this study were 100 respondents. The research sample selection technique used is purposive sampling. Data were collected by using a questionnaire that had been tested for its validity and reliability. The results of this study indicate that social networks supported by a strong local culture have a significant and central role in the formation and maintenance of democratic BUMDes governance. A strong social network will also provide benefits for BUMDes governance that leads to the resolution of financial/economic and managerial issues.